Bioresponsive, Electroactive, and Inkjet-Printable Graphene-Based Inks - Silvestri, Alessandro; Criado, Alejandro; Poletti, Fabrizio; Wang, Faxing; Fanjul-Bolado, Pablo; Gonzalez-Garcia, Maria B.; Garcia-Astrain, Clara; Liz-Marzan, Luis M.; Feng, Xinliang; Zanardi, Chiara; Prato, Maurizio (Advanced Functional Materials, 2022)
With the advent of flexible electronics, the old fashioned and conventional solid-state technology will be replaced by conductive inks combined with low-cost printing techniques. Graphene is an ideal candidate to produce conductive inks, due to its excellent conductivity and zero bandgap. The possibility to chemically modify graphene with active molecules opens up the field of responsive conductive inks. Herein, a bioresponsive, electroactive, and inkjet-printable graphene ink is presented. The ink is based on graphene chemically modified with selected enzymes and an electrochemical mediator, to transduce the products of the enzymatic reaction into an electron flow, proportional to the analyte concentration. A water-based formulation is engineered to be respectful with the enzymatic activity while matching the stringent requirements of inkjet printing. The efficient electrochemical performance of the ink, as well as a proof-of-concept application in biosensing, is demonstrated. The versatility of the system is demonstrated by modifying graphene with various oxidoreductases, obtaining inks with selectivity toward glucose, lactate, methanol, and ethanol.
CRIS-Team Scopus Importer:2023-03-20